Biological nitrogen fixation and nitrogen fertilizer on the nitrogen balance of soybean, maize and cotton - Alves, Bruno José Rodrigues; Zotarelli, Lincoln; Fernandes, Francisco Marques; Heckler, João Carlos; Macedo, Ricardo Antonio Tavares de; Boddey, Robert Michael; Jantalia, Cláudia Pozzi; Urquiaga, Segundo (Pesquisa Agropecuaria Brasileira, 2006)
The subject of this work was to evaluate the effect of biological nitrogen fixation (BNF) of soybean, and the nitrogen fertilizer use efficiency (NFUE) by maize and cotton, on the N balance of an Oxisol (Typic Haplorthox) under no-tillage, in Dourados, MS. The study was carried out for two consecutive years, focusing the summer crops. The BNF contribution to soybean was evaluated by the 15N natural abundance technique. The NFUE was evaluated by the substitution of conventional N fertilizers used for maize and cotton crops by 15N enriched ones. In the first year, both crops were fertilized with 115 kg N ha-1 split in three doses; only plant aerial parts were evaluated. In the second year, only the maize crop was evaluated and received 70 kg ha-1 N, as a dressing fertilization at 29 DAE. In that year, the aerial part of maize plants and the soil of a 0–20 cm layer were evaluated. For two consecutive harvests, the BNF contribution to soybean was over 80%, bringing about high yields and a positive N balance to the soil. In the first year, NFUE for aerial parts of maize and cotton were 48 and 61%, respectively. In the second year, NFUE for maize was 46%, and the soil layer of 0–20 cm also retained 24% of de N fertilizer applied. For the yield levels of maize and cotton, the fertilizer management results in negative N balances to the soil.